OPTIMIZATION OF COOPERATIVE MODELS TYPE OF SEARCH FOR PARTNERS TO IMPROVE STUDENT LEARNING MOTIVATION IN CLASS VI - Siti Maryam (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This research is motivated by the lack of student motivation in learning so that student learning outcomes are low. The purpose of this research is to increase students' motivation in the thematic lessons on the theme of saving sentient beings by applying the cooperative learning model to find a partner. This research was conducted at SDN 04 Bukit Harapan, Kerinci Kanan District, Siak Regency with 21 students consisting of 9 men and 12 women. This research is a classroom action research with research procedures such as planning, implementing, observing, and reflecting. This research was conducted in two cycles. The results showed that student motivation in cycle I was still relatively low with a score of 62 with an average percentage of 4 indicators of learning motivation of 73.8%, while in cycle II it reached a score of 79 with very high criteria, with an average student motivation for learning motivation indicators (4 indicators) of 93.5%. From these results it can be concluded that by applying the type of cooperative learning model to find optimal partners in increasing student motivation.